Application of Changeable Message Signs in Traffic - Ivan Dadić; Goran Kos; Predrag Brlek (Promet (Zagreb), 2003)
In the Republic of Croatia, changeable message signs arebeing introduced on high-serviceability roads in order to improvethe flow management in the network and increase thetraffic safety leveL The equipment installed in the past was notset according to the unique criteria, thus resulting in the installationof relatively incompatible equipment set in a disorganisedmanner. The work presents the basic guidelines in applyingchangeable message signs, primarily on the Croatian motorways.The types and levels of influence on the traffic are described,and the traffic and weather criteria for the applicationof changeable message signs are defined. The paper also analysesthe principles of installing the changeable message signs onroads and road facilities, recommending priorities in presentingthe changeable signs.